Automated refraction is stable 1 week after uncomplicated cataract surgery. Issue 2 (13th December 2017) - Ostri, Christoffer; Holfort, Stig K.; Fich, Marianne S.; Riise, Per
Abstract: Purpose: To compare automated refraction 1 week and 1 month after uncomplicated cataract surgery. Methods: In this prospective cohort study, we recruited patients in a 2‐month period and included consecutive patients scheduled for bilateral small‐incision phacoemulsification cataract surgery. The exclusion criteria were (i) corneal and/or retinal pathology that could lead to automated refraction miscalculation and (ii) surgery complications. Automated refraction was measured 1 week and 1 month after surgery. Results: Ninety‐five patients met the in‐ and exclusion criteria and completed follow‐up. The mean refractive shift in spherical equivalent was −0.02 dioptre (D) between 1 week and 1 month after surgery and not statistical significant (p = 0.78, paired t ‐test). The magnitude of refractive shift in either myopic or hyperopic direction was neither correlated to age, preoperative corneal astigmatism, axial length nor phacoemulsification energy used during surgery (p > 0.05 for all variables, regression analysis). The refractive target was missed with 1.0 D or more in 11 (12%) patients. In this subgroup, the mean refractive shift in spherical equivalent was 0.49 D between 1 week and 1 month after surgery with a trend towards statistical significance (p = 0.07, paired t ‐test). There was no difference in age, preoperative corneal astigmatism, axial length or phacoemulsification energy used during surgery compared to the remainder of the patients (p > 0.05 for all variables, unpaired t ‐test). Conclusion: Automated refraction is stabile 1 week after uncomplicated cataract surgery, but there is a trend towards instability, if the refractive target is missed with 1.0 D or more.